Electrochemical exfoliation of graphite and production of functional graphene. Issue 5 (October 2015) - Yu, Pei; Lowe, Sean E.; Simon, George P.; Zhong, Yu Lin
Abstract: Graphite, being a conductive material, has traditionally been used as an electrode in batteries and other electrochemical devices. In addition to its function as an inert electrode, electrochemical methods have been employed to form graphite intercalation compounds (GICs) and, more recently, to exfoliate graphite into few-layered graphene. The electrochemical methods are attractive as they eliminate the use of chemical oxidants as the driving force for intercalation or exfoliation, and an electromotive force is controllable for tunable GICs. More importantly, the extensive capabilities of electrochemical functionalization and modification enable the facile synthesis of functional graphene and its value-added nanohybrids. This review examines recent progress in electrochemical exfoliation of graphene from graphite. Attention is given not only to the production of pure/pristine graphene sheets, but also to the production of functionalized graphene. Graphical abstract: